Kepuasan Mahasiswa terhadap Biro Administrasi dan Registrasi Akademik di Universitas Stella Maris Sumba - Novebriana Putri Dendo; Friden Elefri Neno; Dian Fransiska Ledi (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
This research aims to analyze the level of student satisfaction with the services provided by the Academic Administration and Registration Bureau at Stella Maris University, Sumba. The method used in this research is a survey with a quantitative approach, where data is collected through questionnaires distributed to students from various study programs. Data analysis was carried out using descriptive statistical techniques to describe the characteristics of respondents and their level of satisfaction with various aspects of service, including speed of service, quality of information, and the attitude of bureau officers. The research results show that the majority of students are satisfied with the services provided, although there are several aspects that need to be improved, such as response time to questions and completeness of the information provided. This research provides recommendations for service improvements, including increased training for bureau staff and the development of more efficient information systems. It is hoped that these findings can contribute to improving the quality of academic administration services at Stella Maris University, Sumba.